Estudo e implantação de um compilador Snobol - Rodrigues, Guilherme Chagas (1971)
Describes the design of a Snobol compiler for the IBM 1130. The structure and organization fo the system is discused from a pratical view point with the objective of making it ready in a short time. The structure and logic of the compilation phase and the runtime environment is presented with a concise description of the main routines. Some facilities of Snobol 3 not implemented are also discussed.